KOMUNIKASI ANTAR PRIBADI STAF PEMBERITAAN TERHADAP KUALITAS BERITA DI LPP TVRI SUMUT - Emmelia A. Ginting; Anastasia Sarah Pasaribu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
This study aims at determining the effect of interpersonal communication of news staff on the quality of news in LPP TVRI North Sumatera. The sample used in this study are as many as 53 people, while the data collection by means of direct interviews guided by the questionnaire. Data analysis was conducted with t-test (partial test). From the results of data analysis, it can be concluded that interpersonal communication has a significant partial effect on the quality of news. Interpersonal communication variables have a positive and significant effect on news quality on Television of Indonesian Republic (TVRI). The coefficient of determination (R²) is 0.387, which means that 38.7% of interpersonal communication variables can improve the quality of news. While the rest is explained by other variables not included as variables in this study